(untitled) (Trabalho & Educação, 2018)
The aim of this work is to examine Antonio Gramsci’s reflections on the need for an intellectual and moral reform, a reform that is conditio sine qua non for the construction of a new hegemony on the part of subaltern social groups. Antonio Gramsci elaborates in the Cadernos do Cárcere the concept of hegemony as the fundamental "theoretical tool" to understand the new configuration assumed by the State in the societies of advanced capitalism, as well as in which resides the exercise of the direction of the dominant social groups. The state in these societies, especially since the second half of the nineteenth century, has become a political society and civil society due to the development of large private organizations of the modern type such as unions, political parties, NGOs. Phase of the state and the dominant groups, since now the exercise of the leadership of the dominant groups is carried out from a combination of coercion and consensus. The State opens channels of social participation for subaltern social groups to present their proposals and to challenge and even incorporate into their policies the demands of these groups, welcomes them and gives them a new meaning. Hegemony is an intellectual direction because it concerns a conception of the world that expresses the interests of a particular social group, presenting it as if manifesting the interests of all social groups. Hegemony is a moral direction because the conceptions of the world imply appropriate forms of behavior and values, forms of behavior and values that, when assimilated by subaltern social groups, become a propitious terrain to guarantee the maintenance and reproduction of Interests of a particular social group. The state that governs on the basis of hegemony can only be overcome from the moment that the subaltern social groups break with these conceptions that they assimilated and are not theirs, conceptions that are the base of the direction of the dominant social groups. In order to break these conceptions and build their hegemony, subordinate social groups need to organize, organize culture, educate themselves, become leaders (specialist + politician). However, there is no organization of culture without intellectuals and it is not possible to build a new hegemony without organizing. Thus Gramsci understands that the construction of hegemony is a process that is neither mechanical nor linear, the construction of hegemony is a "molecular" process and demands an Intellectual and Moral Reformation. But there is no intellectual and moral reform without means and conditions for this, in this sense Gramsci elaborates his conception of Unitary School as homogeneous center of culture aiming at educating the masses in order to making them leaders, preparing them to build their hegemony. Gramsci, when reflecting on the perspectives of social transformation, conceives the construction of hegemony by subaltern social groups, but does not write about counter-hegemony - a concept spread as belonging to his theoretical corpus, but formulated by Raymond Williams. In Quaderni, Gramsci reflects on how to organize culture and carry out an intellectual and moral reform (essential to the conquest of hegemony). In this process, among many interlocutors, the Sardinian thinker dialogues with Georges Sorel and Ernest Renan and their respective concepts "split spirit" and Intellectual and Moral Reform, fundamental to understand the process of building hegemony in Gramsci. ___ O objetivo deste trabalho é examinar as reflexões de Antonio Gramsci sobre a necessidade de uma reforma intelectual e moral, reforma que no seu pensamento é conditio sine qua non para construir uma nova hegemonia por parte dos grupos sociais subalternos. Antonio Gramsci elabora nos Cadernos do Cárcere o conceito de hegemonia como a “ferramenta teórica” fundamental para entender a nova configuração assumida pelo Estado nas sociedades de capitalismo avançado, como também em que reside o exercício da direção dos grupos sociais dominantes. O Estado nessas sociedades, principalmente a partir da segunda metade do século dezenove, configura-se como sociedade política mais sociedade civil devido ao desenvolvimento das grandes organizações privadas do tipo moderno como sindicatos, partidos políticos, ONGs. O desenvolvimento da sociedade civil marca uma nova fase do Estado e dos grupos dominantes, pois o exercício da direção dos grupos dominantes é realizado a partir de uma combinação entre coerção e consenso. O Estado abre canais de participação social para os grupos sociais subalternos apresentarem suas propostas e contestarem e até mesmo incorpora, em suas políticas, reivindicações desses grupos, as acolhe e dá um novo sentido às mesmas. A hegemonia é uma direção intelectual porque diz respeito a uma concepção de mundo que expressa os interesses de um determinado grupo social, apresentando-a como se manifestasse os interesses de todos os grupos sociais. A hegemonia é uma direção moral porque as concepções de mundo implicam formas de comportamento e valores que lhe são adequados, formas de comportamento e valores que, ao serem assimilados pelos grupos sociais subalternos, convertem-se num terreno propício para garantir a manutenção e reprodução de interesses de determinado grupo social. O Estado que governa com base na hegemonia só pode ser vencido a partir do momento em que os grupos sociais subalternos rompem com essas concepções que assimilaram e não são suas, concepções essas que são a base da direção dos grupos sociais dominantes. Para romperem com essas concepções e poderem construir a sua hegemonia, os grupos sociais subalternos precisam se organizar, organizar a cultura, educarem-se, precisam se tornar dirigentes (especialista + político). No entanto não há organização da cultura sem intelectuais e não é possível construir uma nova hegemonia sem se organizar. Assim, Gramsci entende que a construção da hegemonia é um processo que não é mecânico e nem linear, mas “molecular”, demandando uma Reforma Intelectual e Moral. Contudo, não se faz uma reforma intelectual e moral sem meios e condições para tal; nesse sentido Gramsci elabora sua concepção de Escola Unitária como centro homogêneo de cultura com o objetivo de educar as massas para torná-las dirigentes, preparando-as para construírem a sua hegemonia. Quando reflete sobre as perspectivas de transformação social, Gramsci concebe a construção da hegemonia pelos grupos sociais subalternos, mas não escreve sobre contra-hegemonia – conceito difundido como pertencente ao seu corpus teórico, mas que foi formulado por Raymond Williams. Nos Quaderni, Gramsci reflete sobre como organizar a cultura e realizar uma reforma intelectual e moral (imprescindível à conquista da hegemonia). Nesse processo, dentre tantos interlocutores, o pensador sardo dialoga com Georges Sorel e Ernest Renan e seus respectivos conceitos de “espírito de cisão” e Reforma Intelectual e Moral, fundamentais para analisar o processo de construção da hegemonia em Gramsci.